Risk factors that lead to cervical cancer: An integrative review (Research, Society and Development, 2021)
Cervical cancer, also known as cervical cancer, is considered a major health problem that strikes as women on every continent. Given this, the following problem arose: which risk factors contribute to the development of cervical cancer? The objective is to evaluate the risk factors that lead to cervical cancer. This research deals with an integrative review, which was performed using the following databases: Virtual Health Library (VHL), LILACS, SCIELO, MEDLINE and BDENF. The keywords used follow a description of the terms Health Sciences Descriptors (DECS). They were: Factors, Risks, Cervical Neoplasms. For the selection of studies, candidates for inclusion of selected articles (2014-2019), made available in full and with free access to the text and who are familiar with the topic and studies of Portuguese language. According to the findings, it was found that the main factors involved in the onset of cervical cancer were: smokers or former smokers, low income, negative perception of their own health, alcohol use, low education and monthly family income, precocity, not using condoms, parity, low screening coverage, being single and without access to health services. The objectives of the study were satisfactorily achieved, as the results were fully detected by the factors involved in uterine cancer. One of the challenges encountered was the scarcity of related articles.